Regulatory crosstalk between lineage-survival oncogenes KLF5, GATA4 and GATA6 cooperatively promotes gastric cancer development. Issue 5 (22nd July 2014) - Chia, Na-Yu; Deng, Niantao; Das, Kakoli; Huang, Dachuan; Hu, Longyu; Zhu, Yansong; Lim, Kiat Hon; Lee, Ming-Hui; Wu, Jeanie; Sam, Xin Xiu; Tan, Gek San; Wan, Wei Keat; et al.
Abstract : Objective: Gastric cancer (GC) is a deadly malignancy for which new therapeutic strategies are needed. Three transcription factors, KLF5, GATA4 and GATA6, have been previously reported to exhibit genomic amplification in GC. We sought to validate these findings, investigate how these factors function to promote GC, and identify potential treatment strategies for GCs harbouring these amplifications. Design: KLF5, GATA4 and GATA6 copy number and gene expression was examined in multiple GC cohorts. Chromatin immunoprecipitation with DNA sequencing was used to identify KLF5/GATA4/GATA6 genomic binding sites in GC cell lines, and integrated with transcriptomics to highlight direct target genes. Phenotypical assays were conducted to assess the function of these factors in GC cell lines and xenografts in nude mice. Results: KLF5, GATA4 and GATA6 amplifications were confirmed in independent GC cohorts. Although factor amplifications occurred in distinct sets of GCs, they exhibited significant mRNA coexpression in primary GCs, consistent with KLF5/GATA4/GATA6 cross-regulation. Chromatin immunoprecipitation with DNA sequencing revealed a large number of genomic sites co-occupied by KLF5 and GATA4/GATA6, primarily located at gene promoters and exhibiting higher binding strengths. KLF5 physically interacted with GATA factors, supporting KLF5/GATA4/GATA6 cooperative regulation on co-occupied genes. Depletion and overexpression of these factors, singly or in combination, reduced and promoted cancer proliferation, respectively, in vitro and in vivo. Among the KLF5/GATA4/GATA6 direct target genes relevant for cancer development, one target gene, HNF4α, was also required for GC proliferation and could be targeted by the antidiabetic drug metformin, revealing a therapeutic opportunity for KLF5/GATA4/GATA6 amplified GCs. Conclusions: KLF5/GATA4/GATA6 may promote GC development by engaging in mutual crosstalk, collaborating to maintain a pro-oncogenic transcriptional regulatory network in GC cells.